Cascade intramolecular Prins/Friedel–Crafts cyclization for the synthesis of 4-aryltetralin-2-ols and 5-aryltetrahydro-5H-benzo[7]annulen-7-ols - Zheng, Jie (Beilstein J Org Chem, 2021)
The treatment of 2-(2-vinylphenyl)acetaldehydes or 3-(2-vinylphenyl)propanals with BF(3)·Et(2)O results in an intramolecular Prins reaction affording intermediary benzyl carbenium ions, which are then trapped by a variety of electron-rich aromatics via Friedel–Crafts alkylation. This cascade Prins/Friedel–Crafts cyclization protocol paves an expedient path to medicinally useful 4-aryltetralin-2-ol and 5-aryltetrahydro-5H-benzo[7]annulen-7-ol derivatives.